HADIS-HADIS DALAM KITAB HIDĀYAH AL-SĀLIKĪN (Kajian Sanad dan Matn) - Sagir, Akhmad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ine"> </This paper provides an overview and explanation relating to the quality of the existing 190 hadiths in Hidāyah al-Sālikīn of Sheikh Abdus Samad al-Palembani and 51 hadiths added by Shamsuddin Siddiq in the edited book. This research is signifiant to answer the doubts about the quality of existing hadiths in this book, while this book is very popular and used as a reference in a large community. The study shows that the book consists of different quality of hadiths from sahih, hasan, dhaif and mawdu.’<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />